Antihyperlipidemic Effect of a Polyherbal Mixture in Streptozotocin-Induced Diabetic Rats. (5th December 2013) - Ghorbani, Ahmad; Shafiee-Nick, Reza; Rakhshandeh, Hassan; Borji, Abasalt
Abstract : The effects of a polyherbal mixture containing Allium sativum, Cinnamomum zeylanicum, Citrullus colocynthis, Juglans regia, Nigella sativa, Olea europaea, Punica granatum, Salvia officinalis, Teucrium polium, Trigonella foenum, Urtica dioica, and Vaccinium arctostaphylos were tested on biochemical parameters in diabetic rats. The animals were randomized into three groups: (1) normal control, (2) diabetic control, and (3) diabetic rats which received diet containing 15% (w/w) of this mixture for 4 weeks. Diabetes was induced by intraperitoneal injection of streptozotocin (55 mg/kg). At the end of experiment, the mixture had no significant effect on serum hepatic enzymes, aspartate aminotransferase, and alanine aminotransferase activities. However, the level of fasting blood glucose, water intake, and urine output in treated group was lower than that in diabetic control rats (P < 0.01 ). Also, the levels of triglyceride and total cholesterol in polyherbal mixture treated rats were significantly lower than those in diabetic control group (P < 0.05 ). Our results demonstrated that this polyherbal mixture has beneficial effects on blood glucose and lipid profile and it has the potential to be used as a dietary supplement for the management of diabetes.